Clinical and molecular characteristics of acute myeloid leukemia with MPL mutation - Yu Chen (Hematology, 2022)
Objectives The current study aimed to explore the incidence of MPL mutations and the clinical and molecular characteristics of AML with MPL mutation.Methods In total, 1509 patients with newly diagnosed AML were retrospectively analyzed between January 2017 and December 2020. MPL mutations were detected via next-generation sequencing. During the same period, we also enrolled 30 patients with other myeloid neoplasms (MNs) with MPL mutation, which included myelodysplastic syndrome (n = 15), myelodysplastic syndrome/myeloproliferative neoplasm (MDS/MPN) (n = 6), and MPN (n = 9). The clinical characteristics of MPL-mutated AML and other types of MNs or MPL-wide type (MPL-wt) AML were compared, and the spectrum of co-mutations and MPL mutation profiles in MPL-mutated AML were analyzed.Results MPL mutations were identified in 19 (1.26%) of 1509 patients with AML. The waterfall diagram showed that the co-mutations were mainly epigenetic modifications (TET2, IDH1, and EZH2), spliceosomes (SRSF2), and transcription factors (RUNX1). The platelet count of the AML group was significantly lower than that of the MPN group (p = 0.001). MPL mutations were commonly observed in the intracellular region in AML but the transmembrane region in MPN (p = 0.013). The MPL-mutated AML group had a lower white blood cell count and a lower rate of complete remission than the MPL wild-type AML group (p = 0.037).Conclusion MPL mutations are clinically relevant in patients with AML, and they may be a novel subtype characterized by lower white blood cell counts and poor complete remission rates. However, further studies must be conducted to identify its correlated mechanism.